A Rubric to Assess and Improve Technical Writing in Undergraduate Engineering Courses - Maria Asun Cantera; María-José Arevalo; Vanessa García-Marina; Marian Alves-Castro (MDPI AG, 2021)
Although there is consensus in the literature that writing skills are important in STEM (Science, Technology, Engineering, and Mathematics) studies, they are often neglected. However, some efforts have been made to correct this deficiency, one of them being the development of assessment rubrics. This study seeks to contribute to the discussion by presenting the results of the application of a rubric designed to assess the writing skills of a group of 3rd year engineering students. This rubric, which includes linguistic and rhetorical-organizational criteria alongside the mathematical and technical, was used to assess a number of written exercises and essays submitted by students in a 15-week course. The main interest of this study was to test the efficacy of the rubric as a diagnostic tool, conceived to detect the areas of improvement in the students' written performance and, ultimately, to also help them to achieve higher levels of competence. This goal was achieved, as one of the main conclusions of the study is that, although students usually master the technical aspects of the course, they must improve the linguistic and rhetorical aspects of their written communication. It can likewise be said that all the participants involved in the study profited in one way or another from the application of the rubric and contributed to identifying the ways in which the rubric itself can be improved for future application.